Developing Trauma-Informed Capacities in Healthcare Students Staffing Free Clinics - Yang, Phillip; Houser, Jacob; Todd, Jennifer; Plastino, Kristen A; Pearson, Rachel M (Journal of Student-Run Clinics, 2024)
Background: Adverse childhood experiences (ACEs) are common traumatic events experienced during childhood that can have significant and cumulative lifelong impact on health, mental health, and life opportunities. Individuals with marginalized identities experience more ACEs and have greater ACEs-related health burden. Free clinics provide free or low-cost ambulatory care to largely underserved or marginalized communities. Student-staffed free clinic volunteers should be knowledgeable about ACEs and should possess attitudes and engage in practices that promote trauma-informed care. Methods: Two medical students were trained as ACE Interface Master Trainers and administered a training based on the ACEs N.E.A.R. Science curriculum to medical and nursing student free clinic volunteers and leaders. The 1.5-hour training included the Neurobiology and Epigenetics of trauma, health consequences associated with ACEs, and the impact of Resilience in mitigating health consequences of ACEs. Pre-/post-surveys were utilized to measure changes in collective hope, perceived trauma knowledge, and trauma-informed attitudes. Results: The training was administered virtually to one group of medical students and three groups of nursing students (N = 89) between May and October 2020. Two-sample t-tests of the pre-/post-surveys demonstrated statistically significant increases in two of the six collective hope items, six of the six perceived trauma knowledge items, and six of the seven trauma-informed attitudes items. Conclusions: Our study demonstrated that healthcare students volunteering at free clinics have high baseline levels of collective hope, perceived trauma knowledge, and trauma-informed attitudes. A brief and purposeful training on ACEs by peers or near-peers can be effective to further promoting trauma-informed capacities for student-run free clinic volunteers. Future work is needed to ascertain the sustainability of trauma-informed care growth from this training and to measure the effects on care practices.